Cannabinoids from Cannabis sp.: mechanism of their activity and potential health benefits in human body - Dąbrowski, Grzegorz; Skrajda, Marta (Journal of Education, Health and Sport, 2017)
Introduction and purpose: In ancient times, cannabis was used for production of food, edible oil, fibers and medicines. In present, industrial cultivars are the source of raw material for clothing and animal feed. Cannabis can be also a source of psychoactive compounds such as Δ9-tetrahydrocannabinol (THC). Cannabinoids present in Cannabis sp. can cause the beneficial effects in human organism after consumption. This review is aimed to describe the biological properties of cannabis and consider the legalization of marijuana products. Brief description of literature: The endocannabinoid system consists of cannabinoid receptors (CB1 and CB2) and endogenous cannabinoids. CB1 receptors are mostly localized in central nervous system. These receptors are found primarily on central and peripheral neurons in the presynapse. These locations facilitate their inhibition of neurotransmitter release, which is one of the major functions of the endocannabinoid system. CB2 receptors are mostly localized in immune system cells. The interaction of plant cannabinoids with specific receptors can cause several effects in organism. The tissue distribution of CB1 and CB2 is responsible for the well-known psychotropic and peripheral effects of THC. Cannabinoids can be also helpful in treatment in several diseases, such as multiple sclerosis, Tourette syndrome, eating disorders, chronic pain or epilepsy. Conclusions: Despite well-documented health effect of marijuana using, cultivation of cannabis is highly restricted by the law. The main obstacles limiting the use of marijuana in medicine are the psychotropic side effects. In this case, the compromise is difficult to achieve. In future, researchers must cooperate to develop orally administered, highly bioavailable, non-psychoactive phytocannabinoid products.